2007
DOI: 10.1128/jvi.00707-07
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Platform for Prevention of Tuberculosis and Mother-to-Child Transmission of Human Immunodeficiency Virus Type 1 through Breastfeeding

Abstract: Most children in Africa receive their vaccine against tuberculosis at birth. Those infants born to human immunodeficiency virus type 1 (HIV-1)-positive mothers are at high risk of acquiring HIV-1 infection through breastfeeding in the first weeks of their lives. Thus, the development of a vaccine which would protect newborns against both of these major global killers is a logical yet highly scientifically, ethically, and practically challenging aim. Here, a recombinant lysine auxotroph of Mycobacterium bovis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
84
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(88 citation statements)
references
References 56 publications
4
84
0
Order By: Relevance
“…Because of the fact that BCG vaccination has been shown to be safe in newborns, infants, and adults, this bacterium arises as an attractive vaccine vector candidate for recombinant antigens. Indeed, several studies have shown that recombinant BCG strains efficiently induce Th1 responses against several pathogens and diseases (24)(25)(26)(27)(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…Because of the fact that BCG vaccination has been shown to be safe in newborns, infants, and adults, this bacterium arises as an attractive vaccine vector candidate for recombinant antigens. Indeed, several studies have shown that recombinant BCG strains efficiently induce Th1 responses against several pathogens and diseases (24)(25)(26)(27)(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…Construction and preparation of the BCG.HIVA 222 stock was described previously [11]. Briefly, mycobacterial cultures were grown in Middlebrook 7H9 broth medium or on Middlebrook agar 7H10 medium supplemented with albumin-dextrose complex (ADC, Difco) and containing 0.05% Tween 80 and 25 mg/mL kanamycin.…”
Section: Methodsmentioning
confidence: 99%
“…It has been postulated that the resultant phenotypic differences contribute to variable anti-tuberculosis vaccine efficacy [37], although in humans real evidence for this is lacking [38,39]. Previously, we reported the construction of two candidate HIV-1 vaccines BCG.HIVA 401 [13] and BCG.HIVA 222 [11], which employed two distinct BCG strains that were rationally engineered to increase safety and T-cell immunogenicity. and a significant decrease was seen for CCL2 (MCP1) (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycobacterium bovis BCG has been investigated as a live vaccine vector for a variety of human infections (20)(21)(22)(23)(24)(25), including HIV-1 infections (26)(27)(28)(29)(30). An important and attractive feature of using BCG is its long safety record as a tuberculosis (TB) vaccine, having being injected into over 3 billion people worldwide.…”
mentioning
confidence: 99%